Effect of Magnetic Resonance Imaging on Core Body Temperature in Anaesthetised Children. Issue 3 (May 2014) - Lo, C.; Ormond, G.; Mcdougall, R.; Sheppard, S. J.; Davidson, A. J.
Children undergoing magnetic resonance imaging (MRI) often require general anaesthesia (GA). Children under GA are at risk of decreases in body temperature. This risk may be greater during MRI due to MRI scanners requiring cool ambient temperatures. Conversely, radiofrequency radiation emitted by MRI scanners is absorbed by the patient as heat energy, creating a risk of an increase in body temperature. The aim of this study was to determine the proportion of anaesthetised children undergoing an MRI scan who develop hyperthermia or hypothermia, and the risk factors associated with temperature changes in these children. Pre-scan and post-scan tympanic temperatures were obtained from 193 children (aged three months to six years) undergoing an MRI procedure under GA. No active warming or cooling devices were used during the MRI scans. The median duration for anaesthesia was 42 minutes (35 to 57 minutes). Fifty-two percent of children were hypothermic after their scan, while no subjects were hyperthermic after their scan. The mean (± standard deviation) pre-scan temperature was 36.2°C±0.5°C, and the mean (± standard deviation) post-scan temperature was 35.9°C±0.6°C (an overall mean temperature decrease of 0.28°C was observed [95% confidence interval, −0.36°C to −0.19°C], P <0.001). In conclusion, core body temperature was found to decrease slightly during an MRI scan under GA. These results suggest that more focus is needed regarding the cooling effects of GA agents during MRI, as opposed to the heating effects of the MRI scanner.